2019
DOI: 10.1038/s41467-019-09402-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretch induces hair regeneration through the alternative activation of macrophages

Abstract: Tissues and cells in organism are continuously exposed to complex mechanical cues from the environment. Mechanical stimulations affect cell proliferation, differentiation, and migration, as well as determining tissue homeostasis and repair. By using a specially designed skin-stretching device, we discover that hair stem cells proliferate in response to stretch and hair regeneration occurs only when applying proper strain for an appropriate duration. A counterbalance between WNT and BMP-2 and the subsequent two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 58 publications
8
95
2
Order By: Relevance
“…Additionally, macrophages also mediate the sensing of mechanical cues. Stretching skin can polarizes macrophages toward a M2 phenotype [92]. Pro-regenerative M2 macrophages stimulate hair regeneration via paracrine secretion of IGF and HGF.…”
Section: Macrophages For Signaling and For Injury-and Forcesensingmentioning
confidence: 99%
“…Additionally, macrophages also mediate the sensing of mechanical cues. Stretching skin can polarizes macrophages toward a M2 phenotype [92]. Pro-regenerative M2 macrophages stimulate hair regeneration via paracrine secretion of IGF and HGF.…”
Section: Macrophages For Signaling and For Injury-and Forcesensingmentioning
confidence: 99%
“…Macrophages have essential modulatory functions in tissue regeneration [ 29 ]. Indeed, macrophage recruitment is enhanced in the early phase of pulp regeneration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages mainly function in the host defense system to eliminate pathogens by generating pro-inflammatory chemokines and cytokines such as TNF-α, CCL2 and ILs (Saradna et al 2018 ; Murray and Wynn 2011 ) whereas M2 harbors anti-inflammatory properties and engages in ECM remodeling (Mantovani et al 2004 ). Despite the chemical factors, emerging evidence suggests that physical environment contributes to the regulation of macrophage polarization (Fereol et al 2006 ; Pugin et al 1998 ; McWhorter et al 2015 ; Chu 2019 ; Shan 2019 ). As aforementioned, the PF lung exhibits a rigid condition by over deposition of ECM, thus it is reasonable to speculate the cross-talk between alveolar macrophages and the rigid alveolar environment.…”
Section: Main Textmentioning
confidence: 99%
“…Indeed Shan et al showed mechanical stress induces the mouse murine Mφ RAW264.7 cells polarize to M1 via the FAK/NF-κB signaling pathway (Shan 2019 ), considering the deletion of TLR-4 (the major pathway for M1 macrophage activation) manifested increased susceptibility to bleomycin induced lung fibrosis (Jiang et al 2005 ; Paun et al 2010 ). Nevertheless, another group reported that mechanical stress polarized macrophage to M2 phenotype in hair regeneration (Chu 2019 ). This discrepancy could be partially explained as previously reported, a moderate strain was shown to increase the ratio of M2/M1 macrophages over a 7-day period (McWhorter et al 2015 ),while a more extensive strain resulted in marked reduction in M2/M1 macrophages (Ballotta et al 2014 ).…”
Section: Main Textmentioning
confidence: 99%